2019
DOI: 10.1111/dth.12873
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions about oral isotretinoin treatment

Abstract: There are some studies on the knowledge, beliefs, and perceptions of patients about acne vulgaris, however, there is no sufficient data on patients' beliefs about oral isotretinoin treatment (OIT). The aim of this study was to assess the knowledge, beliefs, and perceptions of the patients with acne vulgaris about the therapy of OIT and its side effects. A total of 214 patients with acne vulgaris in our outpatient clinic were included. Patients who were planned to treat with OIT were asked whether they had info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Acne vulgaris is a common, multifactorial, and complex skin disorder that affects the quality of social life in patients 6,9‐11 …”
Section: Discussionmentioning
confidence: 99%
“…Acne vulgaris is a common, multifactorial, and complex skin disorder that affects the quality of social life in patients 6,9‐11 …”
Section: Discussionmentioning
confidence: 99%
“…The teratogenic adverse effects of isotretinoin increases the risk of spontaneous abortion 8 . Even though it has several side effects on multiple systems, effects on the hearing system have rarely been reported 3,5,15,16 . In 1988, Bigby et al reported 104 suspected adverse reactions occurring in 93 patients who took isotretinoin, and they found decreased hearing in one patient who received the therapy and classified this as possibly related to isotretinoin use 3 .…”
Section: Discussionmentioning
confidence: 99%
“…As indicações aprovadas são: acne nódulo-cística grave e pápulo-pustulosa moderada que não melhora com tratamentos convencionais em dois ou três ciclos, recidiva rápida, tendência a cicatrizes e impacto psicossocial negativo (Tugrul, 2019;Vallerand, 2018;Thiboutot, 2018;Landis, 2020). As doses recomendadas são: diária de 0,5 a 1,0 mg/kg, e total de 120 a 150 mg/kg.…”
Section: Indicação E Doseunclassified